2013
DOI: 10.1080/19440049.2012.743189
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of buckwheat flour contaminated by thorn-apple (Datura stramoniumL.) alkaloids: a case study from Slovenia

Abstract: In Slovenia, a mass poisoning incident involving 73 consumers with symptoms such as dry mouth, hot red skin, blurred vision, tachycardia, urinary retention, ataxia, speech disturbance, disorientation and visual hallucinations occurred in 2003. In all cases, consumers had eaten buckwheat flour food products within the last few hours. Investigations by responsible authorities identified the contamination of a range of buckwheat food products with thorn-apple (Datura stramonium L.) seeds containing toxic alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Recently, Perharič et al (2013) reported the presence of substantial amounts of hyoscyamine/atropine and scopolamine in buckwheat flour and buckwheat products collected in retail outlets in Slovenia. Of the 79 samples analysed, 18 contained TAs above the LOQ (30 µg kg -1 ) of the LC-MS/MS method used.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Perharič et al (2013) reported the presence of substantial amounts of hyoscyamine/atropine and scopolamine in buckwheat flour and buckwheat products collected in retail outlets in Slovenia. Of the 79 samples analysed, 18 contained TAs above the LOQ (30 µg kg -1 ) of the LC-MS/MS method used.…”
Section: Discussionmentioning
confidence: 99%
“…Perharič et al (2013b) reported on the analysis of 75 samples of buckwheat grain and buckwheat food products collected from millers and food shops throughout Slovenia. The survey was conducted following food poisoning incidents in 2003 which affected 73 consumers of buckwheat-based food products.…”
Section: Foodmentioning
confidence: 99%
“…As the biosynthesis of these TAs leads to (-)-hyoscyamine and (-)-scopolamine and no stereoselective separation is achieved in this work, analytical results are thus regarded as 100 % (-)-hyoscyamine or (-)-scopolamine. The exposure assessment was part of the risk assessment of buckwheat flour contaminated by thorn apple (D. stramonium) alkaloids carried out in Slovenia after a poisoning incident involving 73 consumers of buckwheat products (Perharič et al, 2013b). The exposure assessment included food samples involved in the outbreak, and it focused on those consumers affected by the poisoning and not on the general population.…”
Section: Previously Reported Human Exposure Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations